Co-Solvent Electrolyte Engineering for Stable Anode-Free Zinc Metal Batteries - Ming, Fangwang; Zhu, Yunpei; Huang, Gang; Emwas, Abdul-Hamid; Liang, Hanfeng; Cui, Yi; Alshareef, Husam N (Journal of the American Chemical Society, 2022)
Anode-free metal batteries can in principle offer higher energy density, but this requires them to have extraordinary Coulombic efficiency (>99.7%). Although Zn-based metal batteries are promising for stationary storage, the parasitic side reactions make anode-free batteries difficult to achieve in practice. In this work, a salting-in-effect-induced hybrid electrolyte is proposed as an effective strategy that enables both a highly reversible Zn anode and good stability and compatibility toward various cathodes. The as-prepared electrolyte can also work well under a wide temperature range (i.e., from −20 to 50 °C). It is demonstrated that in the presence of propylene carbonate, triflate anions are involved in the Zn2+ solvation sheath structure, even at a low salt concentration (2.14 M). The unique solvation structure results in the reduction of anions, thus forming a hydrophobic solid electrolyte interphase. The waterproof interphase along with the decreased water activity in the hybrid electrolyte effectively prevents side reactions, thus ensuring a stable Zn anode with an unprecedented Coulombic efficiency (99.93% over 500 cycles at 1 mA cm–2). More importantly, we design an anode-free Zn metal battery that exhibits excellent cycling stability (80% capacity retention after 275 cycles at 0.5 mA cm–2). This work provides a universal strategy to design co-solvent electrolytes for anode-free Zn metal batteries.